ANALISIS PELUANG DAN ANCAMAN PERDAGANGAN PRODUK PERIKANAN: STUDI KASUS PERDAGANGAN INDONESIA DENGAN TIONGKOK - Larasati, Muti; Daspar, Daspar (At-Tawazun, Jurnal Ekonomi Syariah, 2025)
As an archipelagic country with abundant marine wealth, Indonesia has great potential in developing the fisheries sector as a leading non-oil and gas export commodity. This research aims to analyze the opportunities and threats of trade in Indonesian fishery products with China within the framework of APEC cooperation. The method used is a qualitative descriptive approach with literature studies, using secondary data obtained from various ministry reports, scientific journal articles, economic news, official government websites, and data from international organizations. The results of the study show that although Indonesia has a large export potential for fishery products to China, such as squid, cuttlefish, seaweed, shrimp, and crabs. The country also faces serious challenges in the form of high volumes of imports of low-cost fishery products from China that suppress local prices and weaken the competitiveness of domestic fishermen. Therefore, a comprehensive strategy is needed in the form of improving product quality, diversification, strengthening the processing industry, protecting the domestic market through strict import regulations, and promoting the export of value-added products so that Indonesia can maintain and improve its position in the international fisheries market, especially China.